The Body Adiposity Index is not applicable to the Brazilian adult population - Ribeiro da Costa, José Ronaldo; Costa, Roberto Fernandes da; Goncalves, Ciro Alexandre Mercês; de Oliveira Borges, Michelle Vasconcelos; Almeida-Neto, Paulo Francisco De; De Assis, Gilmara Gomes; Cabral, Breno Guilherme De Araujo Tinoco; Dantas, Paulo Moreira Silva (Frontiers in Nutrition, 2022)
Background: Obesity is a serious disease that burdens public health systems around the world. It is a risk factor for the development of several non-communicable chronic diseases that are related to the amount and distribution of body fat. Body composition assessment using simple and low-cost techniques can help in the early detection of excess fat, allowing for the prevention and treatment of both obesity and associated diseases. Thus, identifying and proposing valid anthropometric indices for this purpose can be a great ally of health programs. Objective: To verify the validity of the Body Adiposity Index (BAI) in relation to Dual Energy X-Ray Absorptiometry (DXA) for estimating body fat percentage in Brazilian adults, as well as proposing a new mathematical model to estimate the fat-free mass of this population. Methods: In a cross-sectional study, 424 subjects (220 women), aged between 20 and 59 years, were evaluated by BAI and DXA, then randomly divided subjects into two groups stratified by sex: the development group (n = 283) and cross-validation group (n = 141). Statistical analyses to test the validity of BAI as a predictor of fat mass, in addition to proposing a new mathematical model for estimating fat-free mass, using DXA as a reference method. Analysis included paired-t test, stepwise multiple regression, coefficient of concordance correlation and Bland-Altman plots. Results: The BAI validity analysis showed a low correlation coefficient of agreement [CCC = 0.626; ρ (precision) = 0.795; Cb(accuracy) = 0.787]; in addition, the mean difference in the Bland-Altman plot was different from zero in the cross-validation group (p < 0.01) and limits of agreement (LOA) ranged between -8.0 and 14.4 kg, indicating a poor agreement between the BAI and the reference method. The new mathematical model for estimating FFM showed a high correlation coefficient of agreement (CCC = 0.952; ρ = 0.953; Cb = 0.999), in addition to acceptable LOA in the Bland-Altman plot (-6.7 and 6.7). Conclusion: In the studied sample, the BAI showed low validity for estimating body fat, while the new proposed model was found to be a good option to assess the body composition of Brazilian adults.